Reexamination of the interaction of atoms with a LiF(001) surface - Miraglia, Jorge Esteban (2017)
Pairwise additive potentials for multielectronic atoms interacting with a LiF(001) surface are revisited by including an improved description of the electron density associated with the different lattice sites, as well as nonlocal electron density contributions. Within this model, the electron distribution around each ionic site of the crystal is described by means of a so-called “onion” approach that accounts for the influence of the Madelung potential. From such densities, binary interatomic potentials are then derived by using well-known nonlocal functionals. Rumpling and long-range contributions due to projectile polarization and van der Waals forces are also included. We apply this pairwise additive approximation to evaluate the interaction potential between closed-shell (He, Ne, Ar, Kr, and Xe) and open-shell (N, S, and Cl) atoms and the LiF surface, analyzing the relative importance of the different contributions. The performance of the proposed potentials is assessed by contrasting angular positions of rainbow and supernumerary rainbow maxima produced by fast grazing incidence with available experimental data. One important result of our model is that both van der Waals contributions and thermal lattice vibrations play a negligible role for normal energies in the eV range.